An observational study on effect of carbon dioxide pneumoperitoneum on liver function test in laparoscopic cholecystectomy - Bellad, Anilkumar; Sahu, Kartik (International Surgery Journal, 2019)
Background: In many studies it was noticed that following a laparoscopic cholecystectomy (LC), liver function parameters were disturbed. The carbon dioxide pneumoperitoneum causes changes in the splanchnic microcirculation and can affect cardiac, pulmonary, liver and kidney physiology. Alterations in intracranial pressure, blood acid- base control and the immune system have also been seen. This study was done to know the effects of carbon dioxide pneumoperitoneum on liver function tests in LC. Aim of the study was to study the significance of alterations in Liver function tests and procedure’s safety Methods: Blood samples of 100 patients who underwent laparoscopic cholecystectomy preoperatively once and post operatively after 24 hours were collected. These blood samples were tested for LFT. The pre op and post op levels of these liver function test values were compared. Results: The level of serum AST, ALT, bilirubin (total) and ALP were increased significantly during the first 24 hrs. Postoperatively after laparoscopic cholecystectomy as compared to baseline values and the levels of serum albumin and total proteins were decreased. Conclusions: There may be a transient elevation of hepatic enzymes after LC and the major causative factor seemed to be CO2 pneumoperitoneum.